The Effect of Roundtable Methods on Narrative Reading: English - Mislawiyadi Mislawiyadi; Sofwil Widad Fuadi (JOEY: Journal of English Ibrahimy, 2025)
Analyzing the impact of the roundtable technique on students' reading abilities was the aim of the study. Quasi-experimental methodology was employed. This study was carried out at MTs Nurul Qarnain Sukowono Jember in the eighth grade. The researchers separated the 64 students into two classes—32 for the experimental class and 36 for the control class—because the population included at least 128 pupils. Roundtable instruction was used in the experimental class, but it was not used in the control classroom. According to the study's findings, students' reading skills improved better when the roundtable technique was used. Its foundation lies in the statistical hypothesis that the p-value, also known as sig (2-tailed) = 0.000, was less than the sig α 0.05. In summary, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Thus, it was demonstrated that the roundtable technique had a considerable and positive impact on eighth-grade MT students' reading abilities. Jember Nurul Qarnain Sukowono